To the question of the differentiation of the opposition coordination / subordination in the research literature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with question of the differentiation of the notions coordination / subordination, composite sentences with transformed semantics are analysed. The author reasons that opposition relations of syntactic unities indicate sencretism of the meaning.
Keywords: complex sentence; compound sentence; syncretism; relations of opposition